Human tail and limb defects: A short tale of a long tail - Balike Krishna Praveen; Kallekkattu Dipu (Wolters Kluwer Medknow Publications, 2015)
A human tail is a congenital, caudal, cutaneous appendage, which usually arises from the tip of the coccyx or it is a finger-like protrusion at the lumbosacral region. It usually indicates the presence of an underlying occult spinal dysraphism. Herein, the authors report a rare case of a human tail, along with multiple anomalies of the limbs in a newborn. The embryological basis for the association is also highlighted.